KINERJA PEGAWAI BALAI BESAR PENINGKATAN PRODUKTIVITAS BEKASI DIPENGARUHI OLEH KOMPETENSI MELALUI MOTIVASI - Eddy Sanusi Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The goal of this study was to analyze and determine the positive and significant influence of competence on employee performance through motivation as an intervening variable. The subject of this research is all employees of Bekasi productivity improvement center by using a quantitative approach method. Meanwhile, to analyze the pattern of relationships between variables in this study, using path analysis with the aim of determine the direct or indirect effect of a set of independent variables on the dependent variable. The findings of the study indicate that competence has a direct impact on Bekasi productivity improvement center employee, as well as an indirect effect through motivation. The performance of the Bekasi Productivity Improvement Center is influenced by competence through motivation.